FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) PADA PASIEN DIABETES MELLITUS - Nurhanifah, Dewi (Ensiklopedia of Journal, 2024)
Abstract: Puskesmas Simpang IV Sipin is one of the health centers with the highest cases of diabetes in Jambi City. The purpose of the study was to determine the factors associated with the utilization of the chronic disease management program (prolanis) in patients with diabetes mellitus. This type of research uses quantitative research with a cross sectional design. The research was conducted in July-August 2023 at the Simpang IV Sipin Health Center. The sample amounted to 77 respondents. The sampling technique used non-probability using purposive sampling technique. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed that there was a relationship between family support (p value: 0.019) and health worker support (p value: 0.007) on prolanis utilization. It is recommended that the community can find information about DM disease and Prolanis, as well as establish communication with officers regarding the implementation of chronic disease programs so that they can take more advantage of Prolanis to keep their health under control to prevent complications from continuing.Keywords: Family support, Diebetes Mellitus, Prolanis.